Pelaksanaan Penyaluran Dana Kampung, Sudahkah Efektif? - Bruri Marwano Wutwensa (Kyadiren, 2022)
This study seeks to examine the effectiveness of village fund distribution, especially in Sawadori Village, Oridek District, Biak Numfor Regency, Papua as well as to examine various causal factors that may affect the implementation of the distribution. This research was empirical juridical research. The results of this study indicate that the effectiveness of fund distribution to Sawadori Village, Oridek District, Biak Numfor Regency is carried out properly. This can be seen from the use of these funds, which are in accordance with Village Minister Regulation (Permendesa) Number 14 of 2020. The factors that influence the effectiveness of managing village funds are the lack of IT Literacy and understanding of village officials regarding the regulations set by the central government, especially during the Covid-19 pandemic